Primary school teachers’ awareness on STEAM learning: A starting point to develop STEAM-CB textbook - Khasanah, Uswatun; Istiandaru, Afit; Astuti, Dwi; Adnan, Mazlini; Prihaswati, Martyana (Universitas Ahmad Dahlan, 2022)
STEAM learning is an approach which integrates multidisciplinary knowledge while enriching students' skills to explore, try, ask, find, and build innovation, namely science, technology, engineering, art, and mathematics. We found that the learning resources of STEAM in Yogyakarta is very limited due to lack of knowledge about it. On the other hand, using local contexts as the starting point of learning is also important to foster character building. This preliminary research aims to provide insight on the teachers’ awareness on STEAM learning and textbook, as well as the design we figured out after discussing it with the teachers. It was a descriptive qualitative research involving 214 primary school teachers. We collected the data through questionnaire and focus group discussion. The results suggest that STEAM is quite a new concept for most of primary school teachers in Yogyakarta. Not many teachers used to or have developed the STEAM learning resources, especially the one integrated with the character building. Therefore, a STEAM textbook needs to be developed to fulfill the need. Furthermore, the design of the textbook could have the characteristics of integrating all components of STEAM (science, technology, engineering, art, mathematics), starting from local context to develop characters, improving creative and critical thinking, having knowledge and skill assessment, and using project-based learning model.